2006
DOI: 10.3354/meps327071
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of nitrogen-fixing cyanobacteria in a Baltic Sea plankton community by land-derived organic matter or iron addition

Abstract: In the Baltic Sea, floating blooms of nitrogen-fixing cyanobacteria occur yearly during late summer. These blooms can sometimes be limited by iron. Due to extensive foresting around the Baltic Sea, iron is entering the Baltic Sea partly bound to dissolved organic material (DOM) via rivers. An experiment was performed in 300 l laboratory mesocosms to test the hypothesis that riverine highmolecular weight dissolved organic matter (HMWDOM), extracted by tangential flow filtration >1000 Da, stimulates the biomass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 30 publications
0
37
1
Order By: Relevance
“…has been described to produce the siderophore schizokinen in response to iron stress (Clarke et al, 1987) as well as the cyanotoxin microcystein that also has siderophore type characteristics (Kaebernick and Neilan, 2006;Utkilen and Gjolme, 1995;Humble et al, 1997). Further, Stolte et al (2006) observed that cyanotoxin production by Nodularia spumigena increases during incubations with combined additions of DOM and Fe. The toxin production of Nodularia spumigena could be a response to increase metal bioavailability in media with strong DOM-metal complexation, where the dissolved iron concentrations are high, but the actual concentration of the bioavailable inorganic iron species (Fe') is low, which also is the case here (Fig.…”
Section: Phytoplankton Bloom Dynamics and Organic Fe(iii)-complexationmentioning
confidence: 60%
See 2 more Smart Citations
“…has been described to produce the siderophore schizokinen in response to iron stress (Clarke et al, 1987) as well as the cyanotoxin microcystein that also has siderophore type characteristics (Kaebernick and Neilan, 2006;Utkilen and Gjolme, 1995;Humble et al, 1997). Further, Stolte et al (2006) observed that cyanotoxin production by Nodularia spumigena increases during incubations with combined additions of DOM and Fe. The toxin production of Nodularia spumigena could be a response to increase metal bioavailability in media with strong DOM-metal complexation, where the dissolved iron concentrations are high, but the actual concentration of the bioavailable inorganic iron species (Fe') is low, which also is the case here (Fig.…”
Section: Phytoplankton Bloom Dynamics and Organic Fe(iii)-complexationmentioning
confidence: 60%
“…remains unclear, but given the shift in the conditional stability constants paralleling the cyanobacterial bloom development during the summer it seems plausible that at least a fraction can be attributed to cyanobacterial toxin and thus ligand production, next to bloom byproducts (TEP, surfactants). Stolte et al (2006) conclude that iron concentrations in the Baltic Sea are sufficient for cyanobacterial growth, but that species composition could be affected by species specific iron acquisition strategies. Our observations of abundance and successive growth of Aphanizomenon sp., Nodularia spumigena, and Anabaena sp.…”
Section: Phytoplankton Bloom Dynamics and Organic Fe(iii)-complexationmentioning
confidence: 99%
See 1 more Smart Citation
“…N 2 -fixing cyanobacteria require high concentrations of Fe and Mo for nitrogenase synthesis, and it has been hypothesised that these elements may limit cyanobacterial growth, particularly in estuaries (Howarth et al 1988). Dissolved organic matter is another factor that has been shown to stimulate the growth of N 2 -fixing cyanobacteria, including Nodularia (Howarth et al 1988, Paerl 1990, Stolte et al 2006. Grazing may therefore stimulate the growth of Nodularia by liberating dissolved organic matter (Moller 2005) and/or metal co-factors from the phytoplankton that they consume.…”
Section: Grazingmentioning
confidence: 99%
“…Alternatively, up-welled phosphorus from deep waters may stimulate growth of cyanobacteria (Kononen et al, 1996;Stal et al, 2003). Iron as a potentially limiting nutrient for cyanobacterial bloom development and nitrogen fixation in the Baltic Sea has been suggested (Stal et al, 1999;Stolte et al, 2006). Nitrogen-fixing cyanobacteria have a Fe demand that is 4-6 times higher than other phytoplankton (Kustka et al, 2002;Sanudo-Wilhelmy et al, 2001) and the development of cyanobacterial blooms may to some degree be regulated by iron bioavailability, as previously suggested for phytoplankton in other coastal regions (Özturk et al, 2002;Hutchins and Bruland, 1998).…”
Section: Introductionmentioning
confidence: 99%